MEASUREMENTS OF ULTRASONIC WAVE VELOCITIES IN ICE CORES FROM GREENLAND AND ANTARCTICA. - Bentley,Charles R.; Bennett,Hugh F. (1965)
The study to measure ultrasonic P and S wave velocities in the ice cores from Greenland and Antarctica was designed to overcome the limitations of the standard methods. The main object of the study was to determine whether the sonic velocity measurements were consistent with the petrofabrics of the ice cores and thereby establish a method of estimating gross crystal orientation by sonic means. In addition, it provided a means of checking the results determined by refraction seismic methods. The comparison of these results indicated the amount of anisotropy present. The determination of wave attenuation as a function of depth also gave a measure of the mechanical filtering properties of the upper layers in the ice sheet. (Author) Prepared in cooperation with Michigan State Univ., East Lansing, Dept. of Geology.